Environmental, Social, and Governance (ESG) Risk Management of PT XYZ Indonesia (ESG Disclosure Approach 2023) - Diva Adisti; Tanti Novianti; Suwarsinah, Heny Kuswanti (Business Review and Case Studies, 2024)
Background: PT XYZ Indonesia is a major mining company facing high risks due to various factors impacting operational, regulatory, and reputational aspects within the mining industry. These risks can be addressed through the company’s responsibility towards environmental, social, and governance (ESG) aspects. In the ESG Disclosure report of 2023, PT XYZ Indonesia was assessed below industry average in several key issues due to inadequate risk management compared to exposure. Purpose: This study aims to identify, assess, and propose appropriate measures to address ESG risks. Methodology: This research using the risk management framework of SNI ISO 31000:2018, with risk assessment methods by Godfrey (1996) and risk treatment strategies by Flanagan and Norman (1993). Results: The research identified 22 ESG risks categorized into three low-level, 12 medium-level, four high-level, and three extreme-level risks. Each risk will be treated according to four categories: retention, reduction, transfer, and avoidance. Risk treatment efforts focused on four high-level risks and three extreme-level risks at PT XYZ Indonesia, including mitigation and transfer strategies to reduce impact and losses experienced by the company. Conclusion: The potential risk most likely comes from Governance Pillar. The practical implications of these proposed strategies include enhanced operational resilience, improved regulatory compliance, and strengthened stakeholder trust, which together contribute to a more sustainable and socially responsible business model. Originality: This study introduces a comprehensive ESG risk management approach by integrating the SNI ISO 31000:2018 framework with established risk assessment and treatment methods, offering a more effective and systematic process for identifying, prioritizing, and mitigating ESG risks. This integrated approach not only enhances the precision and efficiency of risk management but also provides a scalable model for improving ESG performance across the mining sector. Keywords: risk management, mining, ESG Disclosure, ESG Risks, SNI ISO 31000:2018